(untitled) (Medicine Today, 2023)
Introduction: Restoration of effective vision is the principal aim of all modalities of cataract surgery including phacoemulsification. In this method, nuclear part of the cataractous lens is emulsified by ultrasonic power. Energy level of ultrasonic power and turbulence of fluid in the anterior chamber play an important role in corneal endothelial cell loss which inturn influences post-operative corneal clarity. Endothelial cell loss can be minimized by modification of nuclear management method. The common nuclear division techniques of phacoemulsification are stop and chop, divide and conquer and phaco chop. Purpose: To show post-operative corneal clarity after phacoemulsification by stop and chop technique of nuclear divisions. Materials and Methods: This prospective observational study was conducted at selected outdoor patients from January, 2023 to June, 2023 over 33 patients of age related cataract selected for phacoemulsification surgery. Patients were selected based on specific selection criteria. Selected patient underwent detail, ocular and systemic examinations as well as relevant investigations which included assessment of corneal endothelial cell count and central corneal thickness. Phacoemulsification were done in all patients by a single expert surgeon where technique of nuclear management by stop and chop were chosen randomly. Patients were followed up on 1 week, 4 weak and 12 weak after surgery. Corneal endothelial cell count and central corneal thickness were assessed in each visit. All the relevant data were presented by appropriate tables. Results: The mean age of the study subjects were 60.96 with standard deviation 1.75 years out of which 14 were males and 17 were females. Pre-operative value of mean endothelial cell count was 2620+-70.20/mm2. Mean value of endothelial count was 2420+-68.90/ mm2, 2345+-66.64/ mm2, 2310+-66.04/ mm2 respectively after 1 week , 4 weeks and 12 weeks after surgery. Mean value of central corneal thickness was 545+-40.50 micrometer, 535+-40.02 micrometer, 532+-39.85 micrometer respectively after 1 week, 4 weeks and 12 weeks after surgery. Conclusion: Quantitative assessment of endothelial cell count and central corneal thickness shows that at end of the study there was no significant difference in mean endothelial cell count and mean central corneal thickness . Medicine Today 2023 Vol.35(2): 118-120